네팔의 포용적 비즈니스 프로그램 평가에 관한 연구: 경제협력개발기구 개발원조위원회 평가기준 적용을 중심으로 - 김연홍(Yeon-Hong Kim); 이성순(Sung-Soon Lee) (한국콘텐츠학회 논문지, 21(4), 2021)
The Development Assistance Committee of the Organization for Economic Cooperation and Development discusses the reorganization of the five evaluation criteria of the Public Development Assistance Committee, which are used internationally, and the five evaluation criteria including adequacy, efficiency, effectiveness, impact, and sustainability when assessing public development assistance in 1991. This study is to derive alternatives by applying the evaluation criteria of the Development Assistance Committee of the Organization for Economic Cooperation and Development in the evaluation of the inclusive business program being implemented in Nepal since 2019. As a result of the study, the adequacy of Nepal's inclusive business program was consistent with continuous employment and job creation for vulnerable groups such as disabled and orphan women. Efficiency can be said to be efficient in that processes such as work order and work confirmation are made with an electronic management tool, and delivery of the result is transmitted online, saving time and cost compared to other industries. The effectiveness of this project can be said to be an effective program in that it provides high-quality jobs such as providing specialized computer graphics education for the vulnerable, such as disabled and orphan women in Nepal, and hiring graduates as employees. Sustainability is the point that KOICA's inclusive business program has enabled vulnerable groups in the existing fields of agriculture and manufacturing to engage in the computer graphics industry, and the scalability of movies, characters, education businesses, and role models in other countries.However, considering that the scale of public development assistance will continue to increase in the future, it is necessary to establish a systematic monitoring system and a recirculation system so that the project between the donor and recipient countries can continue. 경제협력개발기구 개발원조위원회에서는 국제적으로 통용되는 공적개발원조위원회 5대 평가기준 개편에 대하여 논의하고 1991년 공적개발원조 평가 시 적절성·효율성·효과성·영향력·지속가능성 등 5대 평가 기준의 적용을 권고한 바 있다. 본 연구는 2019년부터 네팔에서 시행 중인 포용적 비즈니스 프로그램의 평가에 있어 경제협력개발기구 개발원조위원회 평가기준을 적용하여 분석하고 개선과제를 도출하는데 있다. 연구 방법은 네팔 현장조사와 포커스 그룹 미팅 방법을 적용하였다. 연구 결과 네팔 포용적 비즈니스 프로그램의 적절성은 장애인, 고아 여성 등 취약계층 대상 지속적인 고용과 일자리 창출에 부합되었고 특히, 한국의 시각적 특수효과에 대한 수요가 증가하는 시점인데다 네팔 취약계층 대상 컴퓨터 그래픽 전문교육을 통한 인력양성이라는 점에서 프로그램이 적정하다고 볼 수 있다. 효율성은 작업지시와 작업컨펌 등의 과정이 전자식 관리 툴로 이루어지고 결과물의 납품이 온라인으로 전송되어 타업종에 비해 시간과 비용이 절감된다는 점에서 효율적이라고 할 수 있다. 효과성은 본 사업이 네팔의 장애인, 고아 여성 등 취약계층 대상 컴퓨터 그래픽 전문교육을 실시하고 수료생을 직원으로 채용하는 등 양질의 일자리를 제공한 점에서 효과성이 있는 프로그램이라고 할 수 있다. 지속가능성은 코이카 포용적 비즈니스 프로그램이 기존 농업, 제조업의 분야에서 종사하는 취약계층들로 하여금 컴퓨터 그래픽 업종에 종사하게 한 점과 영화, 캐릭터, 교육사업의 확장성, 타국가의 롤모델이 될 수 있는 점에서 지속가능성이 있다고 볼 수 있다. 향후 공적개발원조의 규모가 증가할 것을 고려한다면 체계적인 모니터링 시스템과 환류체계의 구축 등 공여국과 수원국 양국간 사업의 지속방안 마련이 요구된다.